Ikan Arwana Sebagai Ide Penciptaan Ukir Relif Kayu - Riky Chandra (VisArt: Jurnal Seni Rupa dan Design, 2025)
This research discusses the process of creating a wood craft artwork with the theme of arowana fish as the main inspiration. The arowana fish was chosen for its distinctive visual form, such as its calm movement, shiny scales, and fan-shaped tail, as well as its meaning in Asian culture as a symbol of prosperity and good fortune. The process of creating this work uses the methods of exploration, design, and realization. The exploration stage involved direct observation of the arowana fish to understand its shape and movements, which were then translated into sketches. The design stage includes selecting the final design and transferring the sketch to surian wood as the main media. In the realization stage, relief carving techniques are applied to produce three-dimensional works with visual depth. The main material used is surian wood, chosen for its strength and beauty of grain, supported by finishing materials such as impra and biopolis to emphasize the texture of the wood. The process involves drawing, cutting, shaping and punching tools to create precise works. The final artwork serves not only as an aesthetic object, but also as a medium of expression and education, highlighting the aesthetic, symbolic and philosophical values of arowana fish. This work represents a combination of high craftsmanship and exploration of cultural values through craft